Evidence for a role of endothelin 1 and protein kinase C in nitroglycerin tolerance. - Thomas Münzel; Adel Giaid; Stephan Kurz; Duncan J. Stewart; David G. Harrison (1995)
We sought to examine mechanisms responsible for increased vasoconstriction that occurs during development of nitroglycerin tolerance. Rabbits were treated for 3 days with nitroglycerin patches (0.4 mg/hr), and their aortic segments were studied in organ chambers. This treatment resulted in attenuated in vitro relaxations to nitroglycerin and increased contractile sensitivity to angiotensin II, serotonin, phenylephrine, KCl, and a direct activator of protein kinase C, the phorbol ester phorbol 12,13-dibutyrate. The protein kinase C antagonists calphostin C (100 nM) and staurosporine (10 nM) corrected the hypersensitivity to constrictors in tolerant vessels, yet had minimal effects on constrictions in control vessels. Paradoxically, constrictions caused by endothelin 1 were decreased in nitrate-tolerant vessels. Immunocytochemical analysis revealed intense endothelin 1-like and big endothelin 1-like immunoreactivity in the media of nitroglycerin-tolerant but not of control aortas. The enhanced vasoconstriction to angiotensin II, serotonin, KCl, and phenylephrine could be mimicked in normal vessels by addition of subthreshold concentrations of endothelin 1, and this effect was prevented by calphostin C. We propose that increased autocrine production of endothelin 1 in nitrate tolerance sensitizes vascular smooth muscle to a variety of vasoconstrictors through a protein kinase C-mediated mechanism.